ASPECTS OF PUBLIC BUS TRANSPORT SERVICE IN RURAL MUNICIPALITIES IN THE DISTRICT OF NITRA (Perner's Contacts, 2014)
The paper deals with the evaluation of transport service by public bus transport inthe rural territories in the district of Nitra by using the selected variables. The firstand basic factor was the number of inhabitants according to which weremunicipalities divided into particular size groups. The mentioned evaluation run onthe basis of geographical and transport indicators that should prove a hypothesisthat the level of transport service increases proportionally with the number ofinhabitants of the municipality, its localization within the district and relations withthe district town that represents the centre of the region.
Keywords: public bus transport; transport service; rural area; district of Nitra